2020
DOI: 10.1111/iwj.13360
|View full text |Cite
|
Sign up to set email alerts
|

PredyCLU: A prediction system for chronic leg ulcers based on fuzzy logic; part II—Exploring the arterial side

Abstract: Peripheral arterial disease (PAD) and its most severe form, critical limb ischaemia (CLI), are very common clinical conditions related to atherosclerosis and represent the major causes of morbidity, mortality, disability, and reduced quality of life (QoL), especially for the onset of ischaemic chronic leg ulcers (ICLUs) and the subsequent need of amputation in affected patients. Early identification of patients at risk of developing ICLUs may represent the best form of prevention and appropriate management. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…An AI-based study by Karimi et al [ 111 ] presented a model to biomechanically characterize atherosclerotic coronary arteries. Fuzzy logic was used to prepare a risk score for the onset of ischemic chronic leg ulcers in PAD patients and natural language processing to better diagnose PAD patients [ 112 , 113 ]. AI methods have also been used among patients suffering from PAD to link them with potential limitations and symptom severity [ 114 ].…”
Section: Artificial Intelligence and Atherosclerosis In Other Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…An AI-based study by Karimi et al [ 111 ] presented a model to biomechanically characterize atherosclerotic coronary arteries. Fuzzy logic was used to prepare a risk score for the onset of ischemic chronic leg ulcers in PAD patients and natural language processing to better diagnose PAD patients [ 112 , 113 ]. AI methods have also been used among patients suffering from PAD to link them with potential limitations and symptom severity [ 114 ].…”
Section: Artificial Intelligence and Atherosclerosis In Other Studiesmentioning
confidence: 99%
“…Seurat uses ML for cell classification. Also, other studies implement SPSS [ 94 , 110 ], PLINK [ 31 , 38 , 41 , 42 ], CARDIoGRAMplusC4D [ 26 , 34 , 37 ], or Ingenuity [ 20 , 23 , 112 ] that are strictly correlated with AI. The search biases are unavoidable as well and the authors are aware of this.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, fuzzy logic is a flexible mathematical system that has been seen considered a powerful tool for decision making and pattern classification in clinical settings. In fact, this mathematical system can allow very fast computations of large sets of heterogeneous data from patients; therefore, it uses a large amount of information [133,134]. Considering heart disease, Garvin et al, in an eight-year follow-up study of a community-based, middle-aged population, showed that plasma MMP-9 levels are able to predict first-time coronary heart disease (CHD) [135].…”
Section: Metalloproteinases and The Paradigm Of Complexitymentioning
confidence: 99%
“…Critical limb ischemia is the most severe form of peripheral arterial disease. It is generally associated with arteriosclerosis, leading to considerable morbidity, mortality, and the loss of quality of life due to disability, which can be aggravated by the occurrence of ischemic ulcers [ 1 , 2 ]. The anatomic and clinical severity of the disease is often heterogeneous and the choice of treatment is affected by different clinical and patient-related factors [ 3 ].…”
Section: Introductionmentioning
confidence: 99%